Interpretation of surgical neuromonitoring data in Canada: a survey of practising surgeons - Norton, Jonathan A. (Can J Surg, 2015)
Intraoperative neuromonitoring is a specialized skill set performed in the operating room to reduce the risk of neurologic injury. There appears to be a shortage of qualified personnel and a lack of Canadian guidelines on the performance of the task. We distributed a web-based survey on the attitude of the surgeons to the interpretation of intraoperative neuromonitoring data among surgeons who use the technique. At present, most of the interpretation is performed by either technologists or by the surgeons themselves. Most surgeons would prefer professional oversight from a neurologist or neurophysiologist at the doctoral level. There is a lack of personnel in Canada with the appropriate training and expertise to interpret intraoperative neuromonitoring data.